Treating Complications of Extracorporeal Life Support in a Patient with COVID-19 (Case Report) - A. S. Rybalko; S. N. Galkina; A. S. Saryglar; V. A. Kolerov; A. V. Voronin; S. N. Perekhodov; N. A. Karpun (Общая реаниматология)
We present a case of mechanical hemolysis as a complication of extracorporeal membrane oxygenation (ECMO) occurring in a COVID-19 patient as a result of pump head thrombosis. After emergency extracorporeal circuit replacement, hemoadsorption was initiated to address the negative hemolysis effects and plasma free hemoglobin rise in the setting of rapid clinical deterioration and impaired renal function. During therapy hemolysis severity reduced, the lactate dehydrogenase (LDH) levels decreased, while the P/F ratio increased two-fold. The patient was discharged from hospital on day 54 without the need for either oxygen therapy or dialysis. In the discussion section we addressed frequent issues of choosing therapy for ECMO complications.Conclusion. The timely, properly chosen, and clinically relevant use of hemoadsorption combined with advanced high-technology therapeutic procedures can have a positive impact on the patient's outcome.